ANALISIS KERJA MESIN CANE UNIGRATOR DENGAN PENGGERAK STEAM TURBINE DI PT. PABRIK GULA RAJAWALI II JATITUJUH - Wardhana, Detta; Dewi Jannati, Eidelweis; Budiman, Haris (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The grinding station is the initial stage of the sugar production activity, the main machine used at this station consists of a cane cutter, a unigrator, and a grinding unit. Before the sugar cane material is entered into the pruning process, the unigrator process is used, which functions as a sugar cane chopper material. The unigrator machine is driven by a steam turbine which is a mover that converts the potential energy of the steam into kinetic energy and is then converted into mechanical energy in the form of a turbine shaft rotation. The purpose of this study was to determine the magnitude of the power needs of the unigrator and to determine the power of the steam turbine driving the unigrator to be able to obtain maximum sugarcane enumeration in PT. Rajawali II Sugar Factory Jatitujuh. The results of the study that analyzed the unigrator machine requires power 69.39 kw / Th, to get the maximum sugarcane count the obtained prepration index value of 93.3%, the higher the prepration index value, the better the performance of the extraction so that the milking process is getting maximum. In the steam turbine produces 160,559 J / sec turbine internal power, the effective power of the turbine generates 1,129 J / sec for the effective power for normal rotation to move the unigrator not too low and its rpm is high.